Skip to content


Open Access

Successive iteration and positive extremal solutions for nonlinear impulsive \(q_{k}\)-difference equations

  • Ravi P Agarwal1, 2Email author,
  • Guotao Wang3,
  • Bashir Ahmad2,
  • Lihong Zhang3 and
  • Aatef Hobiny2
Advances in Difference Equations20152015:164

Received: 7 April 2015

Accepted: 13 May 2015

Published: 3 June 2015


This paper investigates the existence of positive extremal solutions for nonlinear impulsive \(q_{k}\)-difference equations via a monotone iterative method. The main result is well illustrated with the aid of an example.


successive iteration \(q_{k}\)-difference equationimpulsepositiveextremal solutions



1 Introduction

In recent years, there has been put focus on developing the existence theory for initial and boundary value problems of q-difference equations and inclusions. The pioneer work on the topic dates back to the first quarter of the 20th century. In contrast to the classical definition of the derivative, the concept of q-calculus does not involve the idea of limit. The importance of q-difference equations lies in the fact that these equations are always completely controllable and appear in the q-optimal control problems [1]. The q-analog of continuous variational calculus, known as variational q-calculus, is regarded as a generalization of the continuous variational calculus due to the presence of an extra parameter q, which may be physical or economical in nature. The variational calculus on a q-uniform lattice helps to find the extremum of the functional involved in Lagrange problems of q-Euler equations rather than solving the Euler-Lagrange equation itself [2]. The applications of q-calculus appear in several disciplines such as special functions, supersymmetry, control theory, operator theory, combinatorics, initial and boundary value problems of q-difference equations, etc. For details and examples, we refer the reader to the books [36] and [718]. In a recent paper [17], the authors discussed the existence and uniqueness of solutions for impulsive \(q_{k}\)-difference equations. However, it has been found that the study of \(q_{k}\)-difference equations is still at its initial phase and needs further attention.

Motivated by [17], in this paper, we obtain positive extremal solutions for a new class of nonlinear impulsive \(q_{k}\)-difference equations by the method of successive iterations. Precisely, we investigate the following problem:
$$ \begin{cases} D_{q_{k}}u(t)=f (t,u(t) ),\quad 0< q_{k}< 1, t\in J',\\ \triangle u(t_{k})=I_{k} (u(t_{k}) ),\quad k=1,2,\ldots,m,\\ u(0)=\lambda u(\eta)+d,\quad \eta\in J_{r}, r\in\mathbb{Z}, \end{cases} $$
where \(D_{q_{k}}\) are \(q_{k}\)-derivatives (\(k=0,1,2,\ldots,m\)), \(f\in C(J\times\mathbb{R},\mathbb{R^{+}})\), \(I_{k}\in C(\mathbb{R},\mathbb{R^{+}})\), \(J=[0,T]\), \(T>0\), \(0=t_{0}< t_{1}<\cdots<t_{k}<\cdots<t_{m}<t_{m+1}=T\), \(J'=J\backslash \{t_{1},t_{2},\ldots,t_{m}\}\), \(J_{r}=(t_{r},T]\), \(0\le\lambda<1\), \(d\ge0\), \(0\le r\le m \) and \(\triangle u(t_{k})=u(t_{k}^{+})-u(t_{k}^{-})\), \(u(t_{k}^{+})\), and \(u(t_{k}^{-})\) denote the right and the left limits of \(u(t)\) at \(t= t_{k} \) (\(k=1,2,\ldots,m\)), respectively.

The paper is organized as follows. In Section 2, we present some preliminary material and prove an auxiliary lemma, which plays a pivotal role in establishing the main result. Section 3 contains the main result, while an illustrative example is presented in Section 4.

2 Preliminaries

Let us fix \(J_{0}=[0,t_{1}],J_{1}=(t_{1},t_{2}],\ldots ,J_{m-1}=(t_{m-1},t_{m}],J_{m}=(t_{m},T]\) with \(T=t_{m+1}\) and introduce the Banach space
$$PC(J, \mathbb{R}) = \bigl\{ u: J \to\mathbb{R} \mid u\in C(J_{k}), k=0,1, \ldots, m, \mbox{and } u \bigl(t_{k}^{+} \bigr)\mbox{ exist}, k=1,2,\ldots , m \bigr\} $$
with the norm \(\|u\|=\sup_{t\in J} |u(t)|\).

Next we outline some basic concepts of the \(q_{k}\)-calculus [17].

For \(0< q_{k}<1\) and \(t\in J_{k}\), we define the \(q_{k}\)-derivatives of a real valued continuous function f as
$$ D_{q_{k}}f(t) = \frac{f(t)-f(q_{k}t+(1-q_{k})t_{k})}{(1-q_{k})(t-t_{k})}, \qquad D_{q_{k}}f(t_{k})= \lim_{t \to t_{k}}D_{q_{k}}f(t). $$
Higher order \(q_{k}\)-derivatives are given by
$$D^{0}_{q_{k}} f(t) = f(t), \qquad D^{n}_{q_{k}} f(t) = D_{q_{k}} D^{n-1}_{q_{k}} f(t),\quad n \in \mathbb{N}, t\in J_{k}. $$
The \(q_{k}\)-integral of a function f is defined by
$$ {}_{t_{k}}\mathcal{I}_{q_{k}}f(t):=\int _{t_{k}}^{t}f(s)\,d_{q_{k}}s =(1-q_{k}) (t-t_{k})\sum_{n=0}^{\infty}q_{k}^{n}f \bigl(q_{k}^{n}t+ \bigl(1-q_{k}^{n} \bigr)t_{k} \bigr),\quad t \in J_{k}, $$
provided the series converges. If \(a\in (t_{k}, t)\) and f is defined on the interval \((t_{k}, t)\), then
$$\int_{a}^{t}f(s)\,d_{q_{k}} s=\int _{t_{k}}^{t}f(s)\,d_{q_{k}} s-\int _{t_{k}}^{a}f(s)\,d_{q_{k}} s. $$
Observe that
$$\begin{aligned} & D_{q_{k}} \bigl( {}_{t_{k}} \mathcal{I}_{q_{k}}f(t) \bigr)=D_{q_{k}}\int_{t_{k}}^{t}f(s) \,d_{q_{k}} s = f(t), \\ &{}_{t_{k}}\mathcal{I}_{q_{k}} \bigl(D_{q_{k}}f(t) \bigr)= \int_{t_{k}}^{t}D_{q_{k}}f(s)\,d_{q_{k}} s = f(t), \\ &{}_{a}\mathcal{I}_{q_{k}} \bigl(D_{q_{k}}f(t) \bigr)= \int_{a}^{t}D_{q_{k}}f(s)\,d_{q_{k}} s = f(t)-f(a),\quad a\in(t_{k}, t). \end{aligned}$$
In the case \(t_{k} = 0\) and \(q_{k} = q\) in (2.1) and (2.2), then \(D_{q_{k}}f = D_{q}f\), \({}_{t_{k}}\mathcal{I}_{q_{k}}f= {}_{0}\mathcal {I}_{q}f\), where \(D_{q}\) and \(_{0}\mathcal{I}_{q}\) are the well-known q-derivative and q-integral of the function \(f(t)\) defined by
$$D_{q}f(t) = \frac{f(t)-f(qt)}{(1-q)t}, \qquad {}_{0}\mathcal {I}_{q}f(t)=\int_{0}^{t}f(s) \,d_{q} s=\sum_{n=0}^{\infty}t(1-q)q^{n}f \bigl(tq^{n} \bigr). $$

Lemma 2.1

For a given \(\sigma(t)\in C(J,\mathbb{R})\), a function \(u\in PC(J,\mathbb{R})\) is a solution of the linear impulsive \(q_{k}\)-difference equations
$$ \begin{cases} D_{q_{k}}u(t) =\sigma(t),\quad 0< q_{k}< 1, t\in J',\\ \triangle u(t_{k})=I_{k}(u(t_{k})), \quad k=1,2,\ldots,m,\\ u(0)=\lambda u(\eta)+d, \quad \eta\in J_{r}, \end{cases} $$
if and only if u satisfies the following impulsive \(q_{k}\)-integral equations:
$$ u(t) = \textstyle\begin{cases} \int_{0}^{t} \sigma(s)\,d_{{q_{0}}}s+\frac{\lambda}{1-\lambda}\int_{t_{r}}^{\eta} \sigma(s)\,d_{{q_{r}}}s \\ \quad{}+\frac{\lambda}{1-\lambda}\sum_{i=0}^{r-1} \int_{t_{i}}^{t_{i+1}}\sigma(s)\,d_{{q_{i}}}s+ \frac{\lambda}{1-\lambda}\sum_{i=0}^{r}I_{i} (u(t_{i}) ) +\frac{d}{1-\lambda},\quad t\in J_{0};\\ \int_{t_{k}}^{t}\sigma(s)\,d_{{q_{k}}}s +\sum_{i=0}^{k-1}\int_{t_{i}}^{t_{i+1}} \sigma(s)\,d_{{q_{i}}}s +\sum_{i=1}^{k}I_{i} (u(t_{i}) ) +\frac{\lambda}{1-\lambda}\int_{t_{r}}^{\eta} \sigma(s)\,d_{{q_{r}}}s\\ \quad{}+\frac{\lambda}{1-\lambda}\sum_{i=0}^{r-1}\int_{t_{i}}^{t_{i+1}}\sigma(s)\,d_{{q_{i}}}s + \frac{\lambda}{1-\lambda}\sum_{i=0}^{r}I_{i} (u(t_{i}) )+\frac {d}{1-\lambda},\quad t\in J_{k}. \end{cases} $$


As argued in [18], the solution of the \(q_{k}\)-difference equations (2.3) can be written as
$$ u(t)=u(0)+\int_{t_{k}}^{t} \sigma(s)\,d_{{q_{k}}}s +\sum_{i=0}^{k-1} \int_{t_{i}}^{t_{i+1}}\sigma(s)\,d_{{q_{i}}}s +\sum _{i=1}^{k}I_{i} \bigl(u(t_{i}) \bigr),\quad t\in J_{k}. $$
Substituting \(t=\eta\) in (2.5), we have
$$ u(\eta)=u(0) +\int_{t_{r}}^{\eta}\sigma(s)\,d_{{q_{r}}}s +\sum_{i=0}^{r-1} \int_{t_{i}}^{t_{i+1}}\sigma(s)\,d_{{q_{i}}}s +\sum _{i=1}^{r}I_{i} \bigl(u(t_{i}) \bigr), \quad\eta\in J_{r}. $$
Using the nonlocal boundary condition (2.3), we obtain
$$\begin{aligned} u(t) =&\int_{t_{k}}^{t} \sigma(s)\,d_{{q_{k}}}s +\sum_{i=0}^{k-1} \int_{t_{i}}^{t_{i+1}}\sigma(s)\,d_{{q_{i}}}s +\sum _{i=1}^{k}I_{i} \bigl(u(t_{i}) \bigr) +\frac{\lambda}{1-\lambda}\int_{t_{r}}^{\eta} \sigma(s)\,d_{{q_{r}}}s \\ &{} +\frac{\lambda}{1-\lambda}\sum_{i=0}^{r-1}\int _{t_{i}}^{t_{i+1}}\sigma(s)\,d_{{q_{i}}}s + \frac{\lambda}{1-\lambda}\sum_{i=0}^{r}I_{i} \bigl(u(t_{i}) \bigr)+\frac {d}{1-\lambda},\quad t\in J_{k}. \end{aligned}$$

Conversely, assume that \(u(t)\) satisfies the \(q_{k}\)-integral equation (2.4). Then, by employing the operator \(D_{q_{k}}\) on both sides of (2.4) and applying \(t=\eta\), we obtain (2.3). This completes the proof. □

3 Main result

Define a cone \(P\subset PC(J,\mathbb{R})\) by
$$P= \bigl\{ u\in PC(J,\mathbb{R}): u(t)\ge0,t\in J \bigr\} $$
and an operator \(\mathscr{Q}:PC(J, \mathbb{R})\to PC(J, \mathbb{R})\) by
$$\begin{aligned} (\mathscr{Q}u) (t) =&\int_{t_{k}}^{t}f \bigl(s,u(s) \bigr)\,d_{{q_{k}}}s +\sum_{i=0}^{k-1} \int_{t_{i}}^{t_{i+1}}f \bigl(s,u(s) \bigr) \,d_{{q_{i}}}s +\sum_{i=1}^{k}I_{i} \bigl(u(t_{i}) \bigr) \\ &{}+\frac{\lambda}{1-\lambda}\int_{t_{r}}^{\eta}f \bigl(s,u(s) \bigr)\,d_{{q_{r}}}s +\frac{\lambda}{1-\lambda}\sum_{i=0}^{r-1}\int _{t_{i}}^{t_{i+1}}f \bigl(s,u(s) \bigr)\,d_{{q_{i}}}s \\ &{}+ \frac{\lambda}{1-\lambda}\sum_{i=0}^{r}I_{i} \bigl(u(t_{i}) \bigr)+\frac {d}{1-\lambda}. \end{aligned}$$

For the sake of convenience, we introduce some notations and assumptions.

Let \(b,c>0\) be constants and \(R=b+c+\frac{d}{1-\lambda}\).

\(f(t,\cdot)\) is nondecreasing on \(J\times[0,R]\), and \(f(t,u)\le \frac{b}{M}\) on \(J\times[0,R]\), where \(M=T+\frac{\lambda\eta }{1-\lambda}\).


\(I_{k}(\cdot)\), \(k=1,2, \ldots, m\), are nondecreasing on \([0,R]\), and \(I_{k}(u)\le \frac{(1-\lambda)c}{m}\) on \([0,R]\).


\(f(t,0)\not\equiv0\) on any subinterval of J.

We construct two explicit monotone iterative sequences, which converge to positive extremal solutions of nonlinear impulsive \(q_{k}\)-difference equations (1.1):
$$ \begin{aligned} v_{n+1}(t)={}&\int _{t_{k}}^{t}f \bigl(s,v_{n}(s) \bigr) \,d_{{q_{k}}}s +\sum_{i=0}^{k-1}\int _{t_{i}}^{t_{i+1}}f \bigl(s,v_{n}(s) \bigr) \,d_{{q_{i}}}s +\sum_{i=1}^{k}I_{i} \bigl(v_{n}(t_{i}) \bigr)\\ &{} +\frac{\lambda}{1-\lambda}\int _{t_{r}}^{\eta}f \bigl(s,v_{n}(s) \bigr) \,d_{{q_{r}}}s +\frac{\lambda}{1-\lambda}\sum_{i=0}^{r-1}\int _{t_{i}}^{t_{i+1}}f \bigl(s,v_{n}(s) \bigr) \,d_{{q_{i}}}s \\ &{}+\frac{\lambda}{1-\lambda}\sum_{i=0}^{r}I_{i} \bigl(v_{n}(t_{i}) \bigr)+\frac {d}{1-\lambda}, \quad\mbox{with initial value }v_{0}(t)=0, \\ u_{n+1}(t)={}&\int_{t_{k}}^{t}f \bigl(s,u_{n}(s) \bigr)\,d_{{q_{k}}}s +\sum _{i=0}^{k-1}\int_{t_{i}}^{t_{i+1}}f \bigl(s,u_{n}(s) \bigr)\,d_{{q_{i}}}s +\sum _{i=1}^{k}I_{i} \bigl(u_{n}(t_{i}) \bigr) \\ &{}+\frac{\lambda}{1-\lambda}\int_{t_{r}}^{\eta}f \bigl(s,u_{n}(s) \bigr)\,d_{{q_{r}}}s +\frac{\lambda}{1-\lambda}\sum_{i=0}^{r-1}\int _{t_{i}}^{t_{i+1}}f \bigl(s,u_{n}(s) \bigr) \,d_{{q_{i}}}s \\ &{}+\frac{\lambda}{1-\lambda}\sum_{i=0}^{r}I_{i} \bigl(u_{n}(t_{i}) \bigr)+\frac {d}{1-\lambda}, \quad\mbox{with initial value } u_{0}(t)=R. \end{aligned} $$

Recall that a solution \(u^{*}\) of problem (1.1) is called maximal (minimal) if \(u^{*}\ge(\le) u\) holds for any solution u of problem (1.1). The maximal and minimal solutions of problem (1.1) are called its extremal solutions.

Theorem 3.1

If assumptions (H1)-(H3) hold, then the nonlinear impulsive \(q_{k}\)-difference equations (1.1) has positive extremal solutions \(v^{*}\), \(u^{*}\) in \((0,R]\), which can be achieved by monotone iterative sequences defined by (3.2). Moreover, the following relation holds:
$$ v_{0}\le v_{1} \le\cdots\le v_{n} \cdots\le v^{*}\le\cdots\le u^{*}\cdots\le u_{n}\le\cdots\le u_{1}\le u_{0}. $$


By Lemma 2.1, one can transform the nonlocal boundary value problem (1.1) to an equivalent fixed point problem: \(u=\mathscr{Q}u\). That is, a fixed point of the operator equation \(u=\mathscr{Q}u\) is a solution of the problem (1.1).

Obviously, \(\mathscr{Q}:P\to P\). By a similar process to that employed in [18], it is easy to show that \(\mathscr{Q}:P\to P\) is completely continuous.

Denote a ball \(B=\{u\in P,\|u\|\le R\}\). Now, we show that \(\mathscr{Q}(B)\subset B\). Then, for \(u\in B\), by (H1) and (H2), we have
$$\begin{aligned} \bigl|(\mathscr{Q}u) (t)\bigr| =&\int_{t_{k}}^{t}f \bigl(s,u(s) \bigr)\,d_{{q_{k}}}s +\sum_{i=0}^{k-1} \int_{t_{i}}^{t_{i+1}}f \bigl(s,u(s) \bigr) \,d_{{q_{i}}}s +\sum_{i=1}^{k}I_{i} \bigl(u(t_{i}) \bigr) \\ &{}+\frac{\lambda}{1-\lambda}\int_{t_{r}}^{\eta}f \bigl(s,u(s) \bigr)\,d_{{q_{r}}}s +\frac{\lambda}{1-\lambda}\sum_{i=0}^{r-1}\int _{t_{i}}^{t_{i+1}}f \bigl(s,u(s) \bigr)\,d_{{q_{i}}}s \\ &{}+ \frac{\lambda}{1-\lambda}\sum_{i=0}^{r}I_{i} \bigl(u(t_{i}) \bigr)+\frac {d}{1-\lambda} \\ \le&\frac{b}{M} \Biggl[\int_{t_{k}}^{t} \,d_{{q_{k}}}s +\sum_{i=0}^{k-1}\int _{t_{i}}^{t_{i+1}}\,d_{{q_{i}}}s \Biggr] + \frac{k(1-\lambda)c}{m} \\ &{}+\frac{\lambda b}{(1-\lambda)M} \Biggl[\int_{t_{r}}^{\eta} \,d_{{q_{r}}}s+ \sum_{i=0}^{r-1}\int _{t_{i}}^{t_{i+1}}\,d_{{q_{i}}}s \Biggr] +\frac{r\lambda c}{m}+\frac{d}{1-\lambda} \\ \le&\frac{b}{M} \Biggl[t-t_{k}+\sum _{i=0}^{k-1}(t_{i+1}-t_{i}) \Biggr] +\frac{k(1-\lambda)c}{m} +\frac{\lambda b}{(1-\lambda)M} \Biggl[\eta-t_{r}+\sum _{i=0}^{r-1}(t_{i+1}-t_{i}) \Biggr] \\ &{}+\frac{r\lambda c}{m}+\frac{d}{1-\lambda} \\ \le&\frac{bT}{M}+(1-\lambda)c +\frac{\eta\lambda b}{(1-\lambda)M}+\lambda c+ \frac{d}{1-\lambda} \\ \le&R, \end{aligned}$$
which implies that \(\|\mathscr{Q}u\|\le R\). Thus \(\mathscr{Q}(B)\subset B\).
Next, let us denote the iterative sequence \(v_{n+1}(t)=\mathscr{Q}v_{n}(t) \) (\(n=0,1,2,\ldots\)) and pick \(v_{0}(t)=0\). Then \(v_{1}=\mathscr{Q}v_{0}=\mathscr{Q}0\), \(\forall t\in J\). In view of \(v_{0}(t)=0\in B\) and \(\mathscr{Q}:B\to B\), it follows that \(v_{n}\in\mathscr{Q}(B)\subset B \) (\(n=0,1,2,\ldots\)). Thus, we have
$$v_{1}(t)=(\mathscr{Q}0) (t)\ge0=v_{0}(t),\quad \forall t\in J. $$
Applying the conditions (H1) and (H2), it is easy to prove the operator \(\mathscr{Q}\) is nondecreasing.
So, we have
$$v_{2}(t)=(\mathscr{Q}v_{1}) (t)\ge(\mathscr{Q}v_{0}) (t)=v_{1}(t),\quad \forall t\in J. $$
By mathematical induction, one can show that the sequence \(\{v_{n}\}_{n=1}^{\infty}\) satisfies
$$ v_{n+1}(t)\ge v_{n}(t), \quad\forall t\in J, n=0,1,2,\ldots. $$
Similarly, we denote the iterative sequence \(u_{n+1}(t)=\mathscr{Q}u_{n}(t)\) (\(n=0,1,2,\ldots\)) and pick \(u_{0}(t)=R\). Then \(u_{1}=\mathscr{Q}u_{0}\). In view of \(u_{0}(t)=R\in B\) and \(\mathscr{Q}:B\to B\), \(u_{n}\in\mathscr{Q}(B)\subset B\) (\(n=0,1,2,\ldots\)). Thus, by (H1) and (H2), we obtain
$$\begin{aligned} u_{1}(t) =&\int_{t_{k}}^{t}f \bigl(s,u_{0}(s) \bigr)\,d_{{q_{k}}}s +\sum _{i=0}^{k-1}\int_{t_{i}}^{t_{i+1}}f \bigl(s,u_{0}(s) \bigr)\,d_{{q_{i}}}s +\sum _{i=1}^{k}I_{i} \bigl(u_{0}(t_{i}) \bigr) \\ &{}+\frac{\lambda}{1-\lambda}\int_{t_{r}}^{\eta}f \bigl(s,u_{0}(s) \bigr)\,d_{{q_{r}}}s +\frac{\lambda}{1-\lambda}\sum_{i=0}^{r-1}\int _{t_{i}}^{t_{i+1}}f \bigl(s,u_{0}(s) \bigr) \,d_{{q_{i}}}s \\ &{}+\frac{\lambda}{1-\lambda}\sum_{i=0}^{r}I_{i} \bigl(u_{0}(t_{i}) \bigr)+\frac {d}{1-\lambda} \\ \le&\frac{b}{M} \Biggl[\int_{t_{k}}^{t} \,d_{{q_{k}}}s +\sum_{i=0}^{k-1}\int _{t_{i}}^{t_{i+1}}\,d_{{q_{i}}}s \Biggr] + \frac{k(1-\lambda)c}{m} \\ &{}+\frac{\lambda b}{(1-\lambda)M} \Biggl[\int_{t_{r}}^{\eta} \,d_{{q_{r}}}s+ \sum_{i=0}^{r-1}\int _{t_{i}}^{t_{i+1}}\,d_{{q_{i}}}s \Biggr] +\frac{r\lambda c}{m}+\frac{d}{1-\lambda} \\ \le&\frac{bT}{M}+(1-\lambda)c +\frac{\eta\lambda b}{(1-\lambda)M}+\lambda c+ \frac{d}{1-\lambda} \\ \le&R=u_{0}(t),\quad \forall t\in J. \end{aligned}$$
Noting that \(\mathscr{Q}\) is nondecreasing, we have
$$u_{2}(t)=(\mathscr{Q}u_{1}) (t)\le (\mathscr{Q}u_{0}) (t)=u_{1}(t),\quad \forall t\in J. $$
Again, by mathematical induction, it can be shown that the sequence \(\{u_{n}\}_{n=1}^{\infty}\) satisfies
$$ u_{n+1}(t)\le u_{n}(t),\quad \forall t\in J, n=0,1,2,\ldots. $$
By the complete continuity of the operator \(\mathscr{Q}\), the sequences \(\{v_{n}\}_{n=1}^{\infty}\) and \(\{u_{n}\}_{n=1}^{\infty}\) are relative compact. It means that \(\{v_{n}\}_{n=1}^{\infty}\) and \(\{u_{n}\}_{n=1}^{\infty}\) have convergent subsequences \(\{v_{n_{k}}\}_{k=1}^{\infty}\) and \(\{u_{n_{k}}\}_{k=1}^{\infty}\), respectively, and there exist \(v^{*},u^{*}\in B\) such that \(v_{n_{k}}\to v^{*}\), \(u_{n_{k}}\to u^{*}\) as \(k\to\infty\). Using this fact together with (3.5) and (3.6) yields
$$\lim_{n\to\infty}v_{n}= v^{*}, \qquad \lim _{n\to\infty}u_{n}= u^{*}. $$
In consequence, from the continuity of the operator \(\mathscr{Q}\), it follows that \(\mathscr{Q}v^{*}=v^{*}\), \(\mathscr{Q}u^{*}=u^{*}\). This means that \(u^{*}\) and \(v^{*}\) are two solutions of problem (1.1).

Finally, we prove that \(u^{*}\) and \(v^{*}\) are positive extremal solutions of problem (1.1) in \((0,R]\).

If \(w\in[0,R]\) is any solution of problem (1.1), then \(\mathscr{Q}w=w\) and \(v_{0}(t)\le w(t)\le u_{0}(t)\). This implies that \(\mathscr{Q}\) is nondecreasing and that
$$ v_{n}(t)\le w(t)\le u_{n}(t),\quad \forall t \in J, n=0,1,2,\ldots. $$
Thus, employing (3.5)-(3.7), we obtain
$$ v_{0}\le v_{1} \le\cdots\le v_{n} \cdots\le v^{*}\le w\le u^{*}\cdots\le u_{n}\le\cdots\le u_{1}\le u_{0}. $$
In view of \(f(t,0) \not\equiv0\), \(\forall t\in J\), 0 is not a solution of the problem (1.1). Consequently, it follows from (3.8) that \(u^{*}\) and \(v^{*}\) are positive extremal solutions of the nonlinear impulsive \(q_{k}\)-difference equations (1.1) in \((0,R]\), which can be achieved by monotone iterative sequences given in (3.2).

This completes the proof. □

4 Example

Example 4.1

Consider the impulsive nonlocal boundary value problem of the nonlinear \(q_{k}\)-difference equation
$$ \begin{cases} D_{\frac{1}{5+k}}u(t) = f(t,u)=t^{3}+\frac{t}{10} u^{2},\quad t\in [0, \frac{1}{2} ], t\neq\frac{k}{3+k},\\ \triangle u (\frac{k}{3+k} )=\arctan u (\frac{k}{3+k} ) ,\quad k=1,2,\\ u(0)=\frac{1}{8}u (\frac{1}{4} )+\frac{7}{8}, \end{cases} $$
where \(q_{k}=\frac{1}{5+k}\) (\(k=0,1,2\)), \(t_{k}=\frac{k}{3+k}\) (\(k=1,2\)), \(m=2\), \(\lambda=\frac{1}{8}\), \(\eta=\frac{1}{4}\), \(d=\frac{7}{8}\), \(M=\frac{15}{28}\), \(f(t,u)=t^{3}+\frac{t}{10} u^{2}\), and \(I_{k}(u)=\arctan u\). Taking \(b=4-\pi\), \(c=\pi\), \(R=5\), it is easy to verify that all conditions of Theorem 3.1 hold. Hence, by Theorem 3.1, the problem (4.1) has positive extremal solutions in \((0,5]\), which can be achieved by the monotone iterative sequences given by (3.2).



The project was funded by the Deanship of Scientific Research (DSR), King Abdulaziz University, under grant no. 65-130-1435-HiCi. The authors, therefore, acknowledge with thanks DSR technical and financial support. The authors also acknowledge the reviewers for their useful comments.

Open Access This article is distributed under the terms of the Creative Commons Attribution 4.0 International License (, which permits unrestricted use, distribution, and reproduction in any medium, provided you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons license, and indicate if changes were made.

Authors’ Affiliations

Department of Mathematics, Texas A&M University, Kingsville, USA
Department of Mathematics, Faculty of Science, King Abdulaziz University, Jeddah, Saudi Arabia
School of Mathematics and Computer Science, Shanxi Normal University, Linfen, People’s Republic of China


  1. Bangerezako, G: q-Difference linear control systems. J. Differ. Equ. Appl. 17, 1229-1249 (2011) View ArticleMATHMathSciNetGoogle Scholar
  2. Bangerezako, G: Variational q-calculus. J. Math. Anal. Appl. 289, 650-665 (2004) View ArticleMATHMathSciNetGoogle Scholar
  3. Gasper, G, Rahman, M: Basic Hypergeometric Series. Cambridge University Press, Cambridge (1990) MATHGoogle Scholar
  4. Kac, V, Cheung, P: Quantum Calculus. Springer, New York (2002) View ArticleMATHGoogle Scholar
  5. Annaby, MH, Mansour, ZS: q-Fractional Calculus and Equations. Lecture Notes in Mathematics, vol. 2056. Springer, Berlin (2012) MATHGoogle Scholar
  6. Aral, A, Gupta, V, Agarwal, RP: Applications of q-Calculus in Operator Theory. Springer, Berlin (2013) View ArticleMATHGoogle Scholar
  7. Mozyrska, D, Bartosiewicz, Z: On observability concepts for nonlinear discrete-time fractional order control systems. In: New Trends in Nanotechnology and Fractional Calculus Applications, vol. 4, pp. 305-312 (2010) View ArticleGoogle Scholar
  8. Agrawal, O: Some generalized fractional calculus operators and their applications in integral equations. Fract. Calc. Appl. Anal. 15, 700-711 (2012) View ArticleMathSciNetMATHGoogle Scholar
  9. Ismail, MEH, Simeonov, P: q-Difference operators for orthogonal polynomials. J. Comput. Appl. Math. 233, 749-761 (2009) View ArticleMATHMathSciNetGoogle Scholar
  10. El-Shahed, M, Hassan, HA: Positive solutions of q-difference equation. Proc. Am. Math. Soc. 138, 1733-1738 (2010) View ArticleMATHMathSciNetGoogle Scholar
  11. Ahmad, B, Ntouyas, SK: Boundary value problems for q-difference inclusions. Abstr. Appl. Anal. 2011, Article ID 292860 (2011) MathSciNetMATHGoogle Scholar
  12. Ahmad, B, Alsaedi, A, Ntouyas, SK: A study of second-order q-difference equations with boundary conditions. Adv. Differ. Equ. 2012, Article ID 35 (2012) View ArticleMathSciNetMATHGoogle Scholar
  13. Bohner, M, Chieochan, R: Floquet theory for q-difference equations. Sarajevo J. Math. 8(21), 355-366 (2012) View ArticleMathSciNetMATHGoogle Scholar
  14. Ahmad, B, Nieto, JJ: Basic theory of nonlinear third-order q-difference equations and inclusions. Math. Model. Anal. 18, 122-135 (2013) View ArticleMATHMathSciNetGoogle Scholar
  15. Pongarm, N, Asawasamrit, S, Tariboon, J: Sequential derivatives of nonlinear q-difference equations with three-point q-integral boundary conditions. J. Appl. Math. 2013, Article ID 605169 (2013) View ArticleMathSciNetMATHGoogle Scholar
  16. Area, I, Atakishiyev, N, Godoy, E, Rodal, J: Linear partial q-difference equations on q-linear lattices and their bivariate q-orthogonal polynomial solutions. Appl. Math. Comput. 223, 520-536 (2013) View ArticleMathSciNetMATHGoogle Scholar
  17. Tariboon, J, Ntouyas, SK: Quantum calculus on finite intervals and applications to impulsive difference equations. Adv. Differ. Equ. 2013, Article ID 282 (2013) View ArticleMathSciNetGoogle Scholar
  18. Zhang, L, Ahmad, B, Wang, G: Impulsive anti-periodic boundary value problems for nonlinear q k -difference equations. Abstr. Appl. Anal. 2014, Article ID 165129 (2014) MathSciNetGoogle Scholar


© Agarwal et al. 2015